2020
DOI: 10.1262/jrd.2019-151
|View full text |Cite
|
Sign up to set email alerts
|

Intravaginal administration of progesterone using a new technique for sustained drug release in goats

Abstract: The objective of the present study was to develop and evaluate a sustained release vaginal progesterone (P 4 ) capsule containing a mixture of mucoadhesive polymer and silicone fluid. Goats were administered a gelatin capsule containing 0.4 g of P 4 mixed in silicone fluid and either a hydroxypropylmethylcellulose (HM) or polyaclil starch (PA) base. The mean plasma P 4 concentrations at 2 and 12 h after administration were significantly highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The EB capsule was designed to melt immediately after administration and was formulated using commercially available hard fat (Hosco S-55, Maruishi Pharmaceutical Co., Osaka) as the suppository base. The SR EB capsule was designed to melt gradually to reach a peak 24 h after administration and was formulated using an SR base developed previously in our laboratory [9].…”
Section: Preparation Of Intravaginal Estradiol Capsulesmentioning
confidence: 99%
See 3 more Smart Citations
“…The EB capsule was designed to melt immediately after administration and was formulated using commercially available hard fat (Hosco S-55, Maruishi Pharmaceutical Co., Osaka) as the suppository base. The SR EB capsule was designed to melt gradually to reach a peak 24 h after administration and was formulated using an SR base developed previously in our laboratory [9].…”
Section: Preparation Of Intravaginal Estradiol Capsulesmentioning
confidence: 99%
“…The EB capsule was prepared by adding 1 mg of EB powder (Tokyo Chemical Industry Co., Ltd., Japan) and 0.8 ml of hard fat to a gelatin capsule (#00, volume of 1.01 ml, Matsuya Co., Osaka, Japan). For the SR capsule, 1 mg of EB powder and hard fat was placed in a small capsule (#2, volume of 0.37 ml, Matsuya Co., Osaka, Japan) and placed in the center of a large capsule (#00) filled with a SR base containing silicone fluid (Q7-9120, Dow Corning, MI, USA) as a dispersing agent and acrylic starch (SANWET®, Sanyo Chemical Co. Ltd., Kyoto, Japan) as a mucoadhesive polymer [9] (Figure 1). The capsules were then stored at 4C in a refrigerator until administration.…”
Section: Preparation Of Intravaginal Estradiol Capsulesmentioning
confidence: 99%
See 2 more Smart Citations
“…A lower concentration of senktide may have similar effects on the GnRH pulse generator with reduced vaginal leakage. Endo et al [22] reported a sustained drug release technique using a silicon device with progesterone capsules containing a mixture of a mucoadhesive polymer and silicone fluid. To reduce the amount of senktide loss, the chronic administration of senktide using the intravaginal drug delivery system described above should be further evaluated to assess its efficacy using MUA.…”
mentioning
confidence: 99%